Nutritional, Phytochemical and Antioxidant Characterizations of Wild Food and Medicinal Fruits Indigenous to Sudan: Sarcocephalus latifolius and Vitex doniana - Nagwa K-E. M. Salih; Elhadi M. Yahia (International Journal of Fruit Science)
Sudan is a rich country in wild plants that play significant roles in securing food and medicine in rural areas, especially. This study explored Sarcocephalus latifolius (African peach) and Vitex doniana (black plum) for their fruits’ proximate composition, minerals, total soluble phenols, phenolic acids, total carotenoids, lutein, β–carotene, α–tocopherol, δ–tocopherol and total antioxidant capacity. African peach fruit and black plum pulp showed total soluble phenols amounting to 16.89 mg gallic acid equivalents (GAE)/g of Dry Weight (DW) and 7.56 mg GAE/g DW, respectively. The paramount phenolic acids were cinnamic acid (895 mg/kg DW) in African peach fruit and protocatechuic acid (1200 mg/kg DW) in black plum pulp. Total antioxidant capacities reached 268 µmoles trolox equivalents (TE)/g DW in African peach and 214 µmoles TE/g DW in black plum, when measured from hydrophilic extracts (HPE) using 2, 2-DiPhenyl-1-PicrylHydrazyl (DPPH) assay. The contents of total carotenoid were 47 mg/kg DW and 22.6 mg/kg DW, lutein reached 18.50 mg/kg DW and 15 mg/kg DW whereas β–carotene showed 0.31 mg/kg DW and 0.23 mg/kg DW in African peach and black plum, respectively. African peach showed α–tocopherol (167 mg/kg DW) whereas black plum showed δ–tocopherol (398 mg/kg DW). From this study, we concluded that African peach fruit and black plum pulp could be good sources of nutrition and antioxidants and have high potential for human health.